النســق الصـــرفــــــي للسور المكية القصار المتماثلة الفواصل: سورة الأعلى مثالاً - الطريحي, محمد جواد محمد سعيد (Al-Adab Journal, 2019)
After the praise of God and praise him, this study has stood on the blessed Al-Ala Beach, one of the Quranic verses fence which carried increased fatty researchers at several of them and voice morphological and compositional and lexical and semantic levelsThis study was aimed to find a link between linguistic levels that should stand out is a separate - and that unless to mention one of the scholars-namely that the search in the haunted leads to results complement each other, and when it was necessary for each search of Based based upon, the plan we discussed It included a multi-language formats including audio layout and structural and semantic And that will be discussed in turn, has provided the voice pattern that has been deposited for publication in the Journal of the Dean Court today this research comes morphological pattern holds the title of the fence asymmetric spacers and we hope to publish other formats.The study of these formats on the analysis, budgeting and comparison and weighting within the same Sura and ascension to the verses Okhrvi Sormbarkh other had a link to the subject contributes in highlighting his idea and illuminates aspectsOld and modern efforts of scientists has represented tributary Eddt doing research and dressed scientific value, were his sources are many and review, which gave impressive scientific results and sacrificed opto-side Anmazat its fence blessed to be this study, the first of similar actions that could open the way for researchers to enter this field